Adolescents with autism show typical fMRI repetition suppression, but atypical surprise response. (December 2018) - Utzerath, Christian; Schmits, Iris C.; Buitelaar, Jan; de Lange, Floris P.
Abstract: Recent theoretical frameworks have hypothesized that autism spectrum disorder (ASD) may be marked by an altered balance between sensory inputs and prior knowledge–the so-called hypoprior hypothesis. Yet evidence regarding such an altered balance is mixed. Here, we aimed to test this hypothesis within the domain of visual perception, by examining how neural activity in the visual system was modulated by stimulus repetition and stimulus expectation in healthy and ASD participants. We presented 22 adolescents with ASD and 22 typically developing (TD) adolescents with pairs of object stimuli, while measuring brain activity using functional magnetic resonance imaging (fMRI). Stimulus pairs could be stimulus repetitions or not and could be expected or not. We examined neural activity in early (V1) and object-selective (LOC) visual cortex. Both ASD and TD individuals showed robust and equal repetition suppression in LOC. By contrast, ASD and TD groups showed a different response to expected versus unexpected stimuli, specifically in V1. Thereby, our results suggest that while the more automatic modulation of activity by repetition is unaffected in ASD, there is some evidence that the balance between sensory evidence and prior knowledge may indeed be altered in early visual cortex of ASD.